318 Management of Incidental Pancreatic Cysts –Are We Adhering to Guidelines?. (4th May 2021) - Sharmin, A; Ahmed, R; Singhal, T; Kumar, M
Abstract: Background: The majority of pancreatic cysts (PC) are incidentally diagnosed. Most NHS Trusts do not have pathways to manage them. We reviewed the management of incidental PC and adherence to guidelines. Method: Data was collected across three hospitals in our Trust between January 2018-January 2019 when there were no guidelines. Reaudit was performed between July 2019-February 2020 following the introduction of trust guidelines that recommend all PC be discussed in MDT meetings. Results: The first audit identified 79 patients and 28 in the second. 53% (42) and 64% (18) patients were referred to HPB/GI MDT during the two periods. There was an 11% increase in MDT referrals, however, 35.71% of patients were still not referred. During the initial audit, 62 % (23/37) of patients in the Non-MDT group had no surveillance scans, potentially missing high-risk patients and 38% of patients (14/37) still underwent surveillance scans from non-GI specialists which could be unnecessary. 44% of patients underwent surveillance following MDT in the second period as compared to 83% prior to guidelines (p = 0.002). Conclusions: Robust guidelines for incidental PC identify high risk cysts that warrant future surveillance/treatment and avoid unnecessary scans releasing radiology capacity.MDT referral ensures malignant transformations are identified early and reduce morbidity and mortality.